Effect of welding motion and pre-/post-annealing of friction stir welded AA5754 joints. (5th March 2016) - Cabibbo, M.; Forcellese, A.; Simoncini, M.; Pieralisi, M.; Ciccarelli, D.
Abstract: An innovative approach to the friction stir welding process (defined by authors as RT-type configuration) of AA5754 sheets, characterized by a welding motion of the pin tool obtained by the combination of two different movements occurring simultaneously, was developed. Such novel approach was compared with the conventional friction stir welding process (T-type configuration). Tools with different pin heights were used in order to obtain different sinking values. Finally, the influence of the annealing treatment, prior and after the friction stir welding process, was studied. The effect of process parameters and annealing treatment on the microstructure, micro- and macro-mechanical properties of friction stir welded joints obtained under RT-type and T-type configurations was widely investigated. This way, the process condition and the temper state that allow obtaining defect-free joints, without the occurrence of the oxide defects of kissing-bonds, and faint zigzag line pattern in the NZ, was defined. It resulted that a pin deviation by R = 0.5 mm, from welding centerline, in the post-welded annealed condition, showed better tensile strength, respect to the conventional (T-type) welding. Graphical abstract: Highlights: A new friction stir welding process of AA5754 was presented. The role of the pin deviation from welding centerline was characterized. Influence of the annealing treatment was determined. Microstructure and microhardness tests were performed. The pin deviation had beneficial role in the post-welded annealed joints.